Залежність оптичних властивостей тонких Ag2S плівок на оксиді індію-олова, виготовлених осадженням за допомогою лазерних імпульсів, від енергії лазера - Hamid, L. A.; Dwech, M. H.; Aadim, K. A. (Publishing house "Academperiodika", 2020)
Nanocrystalline silver sulfide (Ag2S) thin films were prepared by the pulse laser deposition technique (PLD) on the indium-tin oxide (ITO) substrate at room temperature. In the PLD technique, an Nd : YAG laser with a wavelength of 1064 nm at different laser energies from 400 to 900 mJ is used with an increment of 100 mJ in each step with 200 pulses for each sample. The optical properties such as the refraction index n, absorption coefficient a, and extinction coefficient k are examined using the transmission and absorbance measurements on a UV-Vis-NIR spectrophotometer in the wavelength range (200–1100) nm. The average extinction coefficient is found between 0.076–0.163, while the average refractive index is between 2.214–2.528. The energy band gap decreases from 2.39 to 1.9 eV with increasing the laser energy.